Uptake of routine growth monitoring among children under 9 months in Nyamira County, Kenya - Nyangechi, Edna Nyanchama; Yitambe, Andre; Rucha, Kenneth Kibaraa; Osero, Justus O. S. (International Journal Of Community Medicine And Public Health, 2019)
Background: The health and nutritional status of children can be assessed through routine growth monitoring (RGM). This provides opportunities for implementation of interventions aimed at reducing under five mortality rates, infectious diseases and malnutrition. The objective of the study was to find out the level of uptake of routine growth monitoring among caregivers of children aged below 9 months in Nyamira County, Kenya. Methods: This was a cross-sectional study. Results: Only 21.1% of the caregivers consistently took their children for RGM. About 78.9% of caregivers had skipped RGM visits for their children in the last eight months at least once or more. About 45.8% of caregivers skipped RGM visits twice, 31.7% thrice, 20.4% once and 2.1% skipped four times. Uptake of RGM was not significantly associated with caregivers’ level of education (p=0.052), marital status (p=0.099), occupation (p=0.081), monthly income (p=0.941), distance to nearby health facility (p=0.774) and place of residence (p=0.330). Caregivers who skipped RGM visits gave various reasons including forgetting to come again dates (91.5%), child not sick (77.5%), healthcare providers advising them not to go for RGM since there was no scheduled vaccination (67.6%), among others. Conclusions: There is need for healthcare providers capacity building on their role in improving RGM since most of them discourage caregivers unless for those with scheduled immunization. Policy makers and implementers in the health sector should formulate relevant policies especially targeted at reminding caregivers on monthly RGM for their children aged below 9 months.